2017
DOI: 10.1017/s1092852917000074
|View full text |Cite
|
Sign up to set email alerts
|

Lurasidone for major depressive disorder with mixed features and anxiety: a post-hoc analysis of a randomized, placebo-controlled study

Abstract: Objective. The aim of this post-hoc analysis was to evaluate the efficacy of lurasidone in treating patients with major depressive disorder (MDD) with mixed features who present with mild and moderate-to-severe levels of anxiety.Methods. The data in this analysis were derived from a study of patients meeting the DSM-IV-TR criteria for unipolar MDD, with a Montgomery-Åsberg Depression Rating Scale (MADRS) total score ≥26, presenting with two or three protocol-defined manic symptoms, who were randomized to 6 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…A pooled analysis of two double‐blind RCTs demonstrated that quetiapine is more effective than placebo in relieving symptoms of anxiety co‐occurring alongside bipolar depression,313 and olanzapine‐fluoxetine combination has also been shown to be effective 314. In a post hoc analysis, lurasidone was effective in improving depressive as well as anxiety symptoms in patients with MDD who had mixed features and anxiety 315. The anxiolytic effects of divalproex, risperidone, and lamotrigine appear to be limited 199, 316…”
Section: Acute Management Of Bipolar Depressionmentioning
confidence: 99%
“…A pooled analysis of two double‐blind RCTs demonstrated that quetiapine is more effective than placebo in relieving symptoms of anxiety co‐occurring alongside bipolar depression,313 and olanzapine‐fluoxetine combination has also been shown to be effective 314. In a post hoc analysis, lurasidone was effective in improving depressive as well as anxiety symptoms in patients with MDD who had mixed features and anxiety 315. The anxiolytic effects of divalproex, risperidone, and lamotrigine appear to be limited 199, 316…”
Section: Acute Management Of Bipolar Depressionmentioning
confidence: 99%
“…Low dosages, moreover, may have contributed to good tolerability: nausea and somnolence were the two most frequently reported adverse events (NNH of 8 for both). Post-hoc analyses showed that lurasidone is significantly useful in subgroups with mild and moderate-to-severe anxiety (Tsai et al, 2017), subjects with irritability (Swann et al, 2017) and post-menopausal women (Sramek et al, 2017).…”
Section: Major Depressive Disorder With Mixed Featuresmentioning
confidence: 99%
“…43 Other common manic symptoms were irritability and distractibility. Post-hoc analyses of study data found that lurasidone also improved irritability 44 and anxiety symptoms 45 in this patient population without adversely affecting sexual function. 46 Additionally, lurasidone was associated with greater rates of response and remission 47 and was efficacious in post-menopausal women with major depressive disorder with mixed features.…”
Section: Randomized Placebo-controlled Controlled Trials In Protocoldefined Mixed Depressionmentioning
confidence: 76%